Cellulose-containing waste recycling using fungi - I. A. Fomenko; S. N. Tuchkova (Новые технологии)
Accumulation of plant waste is a serious environmental problem. Mushrooms with high cellulolytic activity can process it into valuable products that will be useful in solving various industries and agriculture problems. The enzymes of the cellulolytic complex include 1,4-β-D-glucan-4-glucanohydrolase, exo-1,4-β-glucosidase, cellobiohydrolase, β-glucosidase. 1,4-β-D-glucan-4-glucanohydrolases destroy β-1,4-glycosidic bonds within the chain of cellulose and lichenin polysaccharides. Exoglucanases destroy β-1,3- and β-1,4-glycosidic bonds at the end of the molecule. Cellobiohydrolases cleave β-1,4-glycosidic bonds to form cellobiose and glucose. β-glucosidase complete the process of destruction. Fungi with high cellulolytic activity include both representatives of the Ascomycota and Basidiomycota divisions. Ascomycete Chaetomium globosum produces endoglucanases of two families and 8 cellobiohydrolases. Myceliophthora thermophila also produces endoglucanases and cellobiohydrolases, the most abundant of which is Mt Cel7A. The fungus is a promising producer of thermostable enzymes. Trichoderma reesei has a long history of safe use as a source of highly active cellulolytic enzymes and other valuable metabolites. LPMOs of the cellulolytic fungus Thielavia terrestris are considered auxiliary enzymes, but can negatively affect the main enzymes of the complex. Irpex lacteus also produces LPMO and a complete cellulolytic enzyme complex. The cellulolytic activity of fungi and their ability to grow on cheap substrates can be used to bioconvert plant waste into valuable products. One of the ways to utilize them is to convert into compound feed with a high protein content through the use of starter cultures. The use of mushrooms will increase the content of protein and simple carbohydrates, enrich the feed with fats. Another method is to obtain cellulases, which are widely used in many industries. Thanks to the production of biodiesel and bioethanol from cellulose-containing raw materials it is possible to solve the problem of lack of fuel by replacing energy carriers from non-renewable energy sources with their environmentally friendly counterparts. They are less toxic than diesel and gasoline and are also made from renewable resources.